Evaluations of haemostatic alterations in coronary artery bypass graft patients before and after angiography using thrombelastography - (:unkn) unknown (My University, 2013)
The Thrombelastograph™ (TEG) provides a global assessment of blood coagulation. The study aim was to evaluate the dynamic haemostatic parameters utilizing TEG in blood specimens of hyperlipidemic patients (n=22) and healthy donors (n=15) before and 30 min after the angiography. Such TEG parameters as: reaction time (R, min), clot formation time (K, min), fibrinogen activity (Angle, degree), clotting maximum amplitude (MA, mm), and clotting index (CI) were quantitated. The patients' values before vs. after the angioplasty were: R = 4.74±1.59 vs. 3.36±0.89 min (5.48±1.39 min for control), K = 2.77±2.45 vs. 1.75±0.95 min (1.57±0.24 min for control), Angle = 64.38±11.21 vs. 69.72±8.22 degree (67.13±6.67 degree for control), MA = 52.2±16.94 vs. 57.84±9.46 mm (59.97±4.73 mm for control), and CI = 0.31±2.59 vs. 1.71±2.07 (0.22±2.14 for control). It is clear that the risk ratio was lowered in patients after the angiography where increased haemostatic defects were detected before the angiography.
Keywords: Angiography; Coronary artery bypass graft; Haemostatic system; Thrombelastography